THE INFLUENCE OF ENVIRONMENTAL POLICIES ON SELECTING INVESTMENT LOCATIONS - Anita Sitawati; Herika Muhammad Taki; Rezkia Dewi Andajani (Universitas Trisakti, 2022)
Globalization causes multinational entrepreneurs to move their business locations across geographical boundaries. The Multinational Entrepreneurs running businesses across geographic boundaries are called Foreign Direct Investment (FDI). One factor that determines the success of FDI is the accurate choice of investment location. Currently, Climate Change plays a significant role in business decisions. Aim: This study aimed to assess the selection of investment locations using the demand-side analysis and environmental policies approach. Methodology and results: The sample was the Electronic and Automotive industry located in the JABABEKA Industrial Estate, Jakarta, Indonesia. The primary data were collected from the respondents' perceptions and processed using the Structural Equation Model (SEM) method. The SEM-PLS results showed that the path coefficient of the relationship between Environmental Regulations and the Investment Locations Choice was 0.314. Therefore, Environmental Regulation significantly affected Investment Locations Choice. Furthermore, the path coefficient of the relationship between Environmental Litigation and the Investment Locations Choice was 0.113, with a P-value > 0.05. This means that Environmental Litigation insignificantly affects the Investment Locations Choice. Conclusion, significance, and impact: Environmental regulations and litigation affect the location selection by investors. Therefore, urban planners should formulate policies for providing better waste and air pollution treatment facilities in each industrial area to increase the attractiveness of Indonesia as a Host Country.